PERANCANGAN WEBSITE MONITORING GANGGUAN INTERNET DAN MENGGUNAKAN UML (STUDI KASUS: PT. FAZNET) - Irfan, Muhamad; Nasrullah, Dinda Maharani; Angelina, Viola; Setiawan, Rahmat; Hafiz, Fakhri (JURNAL ILMIAH INFORMATIKA, 2025)
This research brings to light an urgent dilemma pervading the broadband service supplying sector exemplified by PT. Faznet.Presently, clients have difficulties effectively communicating interruptions owing to manual processes providing scant network performance information. Addressing this communication vacuum, we propose a wireless network monitoring web portal engineered to dynamically present internet conditions in real time (speed, signal quality, status) and enable two-way interactions through disturbance reporting, maintenance advisories, and status updates. The developmental approach applies the Unified Modeling Language (UML), starting with Use Case Diagrams to model user requirements, progressing to Activity Diagrams detailing work processes, Sequence Diagrams sequencing intercomponent operations, and lastly Class Diagrams outlining software structure. It is expected that implementing this system will notably amplify transparency and responsiveness to better serve customers of PT. Faznet. This paper investigates a key challenge in sharing network performance data and service issues with subscribers of an internet provider. The suggested remedy involves designing an online dashboard displaying current network metrics and a feedback mechanism for users and technicians to exchange information on problems, repairs, and network status. System architecture and evolution adheres to modeling best practices to map workflows, message passing, and class relationships with the goal of vastly improving availability of network intelligence to customers while strengthening support reactivity. This aims to boost satisfaction levels among the user base of the featured broadband corporation.